199. The Urgent Need for Urgent Care Antimicrobial Stewardship: Evaluating Prescribing and Patient Outcomes Associated with a Pharmacist-led Stewardship Program. (26th November 2018) - Fay, Lauren; Wolf, Lauren; Brandt, Kasey; Deyoung, G Robert; Anderson, Adam; Egwuatu, Nnaemeka; Dumkow, Lisa
Abstract: Background: Antimicrobial resistance is one of the most serious threats to public health. Antimicrobial stewardship initiatives have begun to expand from acute care to ambulatory care settings. While many programs have demonstrated pharmacist-led stewardship successes in inpatient and emergency department (ED) settings, there is a paucity of literature exploring these initiatives in urgent care (UC) sites. This study aimed to determine the impact of implementing a pharmacist-led antimicrobial stewardship program (ASP) in the UC setting. Methods: A retrospective quasi-experimental study was conducted evaluating patients from two health system-affiliated UC sites with positive urine or wound culture results following discharge. In April 2015, the health system's infectious diseases and ED pharmacists, with support from UC providers, implemented empiric therapy guidelines and a collaborative practice agreement allowing for pharmacist-led culture follow-up via a stewardship-focused protocol. The primary outcome of this study was to compare guideline-concordant antibiotic prescribing (defined as the combination of appropriate agent, dose, and duration of therapy) between the pre-ASP and post-ASP groups. Secondary outcomes included comparing the number of patients who required follow-up, time to follow-up, UC or ED revisits within 72 hours, and hospital admission within 30 days between groups. Results: Three hundred patients were included in the study (pre-ASP n = 150, post-ASP n = 150). Total guideline-concordant prescribing for all diagnoses was significantly improved in the post-ASP group compared with the pre-ASP group (41.3% vs. 53.3%, P = 0.037). Guideline-concordant antibiotic selection improved in the post-ASP group (51% vs. 68%, P = 0.01) while dose (70 % vs. 74%, P = 0.287) and duration (61% vs. 65%, P = 0.283) were similar between groups. Follow-up was required for 27 (18%) patients in the pre-ASP group vs. 16 (10.7%) in the post-ASP group ( P = 0.07), however median time to follow-up call was longer in the post-ASP group (71 vs. 38 hours, P < 0.001). There were no differences between groups in UC ( P = 1.0) and ED revisits ( P = 1.0) within 72 hours or hospital admissions within 30 days ( P = 0.723). Conclusion: A pharmacist-led urgent care ASP was associated with significantly improved guideline-concordant antimicrobial prescribing. Disclosures: All authors: No reported disclosures.